1984
DOI: 10.1159/000241780
|View full text |Cite
|
Sign up to set email alerts
|

Development of Enzymes of Energy Metabolism in Rat Heart

Abstract: The behavior of several enzymes was studied during rat heart development (4 days before birth to adult stage). Hexokinase has its highest activity during the fetal period; it decreases at birth and remains with low activity in the adult. The α-glycerophosphate dehydrogenase and α-glycerophosphate oxidase profiles are similar up to the 15th day of development. From there onwards, both profiles diverge, the cytoplasmic activity increasing 3-fold, while the mitochondrial activity remains unchanged. The developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…A rise in mitochondrial numbers is consistent with previous studies [22] and reflects the increased energy demand of mature myocardium.…”
Section: Discussionsupporting
confidence: 92%
“…A rise in mitochondrial numbers is consistent with previous studies [22] and reflects the increased energy demand of mature myocardium.…”
Section: Discussionsupporting
confidence: 92%
“…Myocardial HK activity differs among species and exhibits the transmural gradient [48,49]. It was reported that HK exhibits the maximal enzyme activity in the heart during the fetal period and only moderate changes occur during postnatal life [50,51]. Although higher activity of HK in the RV compared to the LV was found in young rats [49,51], other studies did not detect any significant right-to-left ventricular difference [52,53,54] according to results of the present work.…”
Section: Discussionmentioning
confidence: 99%
“…It is belived, that this isoform permits rapid ADP/ATP exchange across the inner mitochondria] membrane [30, 311. The data presented here demonstrate clearly that changes in the matrix adenine nucleotides and in the AAC protein are important factors in the postnatal maturation of oxidative phosphorylation. On the other hand, enrichment of the F,F,-ATP synthase [24, 251, of the respiratory chain complexes [32,331, of the hydrogen-supplying enzymes (citric acid cycle enzymes [ 321, pyruvate dehydrogenase complex [ 341, P-oxidation enzymes [35]), the mitochondrial creatine kinase [36] in mitochondria and the reduction of the passive proton permeability of the inner mitochondrial membrane [8] also contribute to this process. Interestingly, the reduction in the passive proton permeability of the inner mitochondrial membrane during postnatal development has been attributed to the interaction of the AAC with the matrix adenine nucleotides [37].…”
Section: Discussionmentioning
confidence: 99%